heh i've calmed down a bit so let's see if I can get this.

Mind if we use a different problem?

y = -f(2x) , It would horizontally shrink by 1/2 and reflect across the x-axis

y = f(2x) - 1 , It would horizontally shrink by 1/2 and vertically shift down one unit.

Did i get those right?

Also if those two were supposedly written in function notation, how would it look?

I'm curious because for instance

y = 2f(x + 2) - 2 is the same as f(x) = 2(x + 2) - 2 where both would horizontally shift two units to the right, vertically shift 2 units down and vertically stretch by 2.

So

How would y = f(4x) or y = f(2x) - 1 look if it were to start with

F(x) =

sorry if it's a stupid question but I'm curious =/